Self-care and type 2 diabetes mellitus (T2DM): a literature review in sex-related differences - Baroni, Irene; Caruso, Rosario; Dellafiore, Federica; Ausili, Davide; Barello, Serena; Vangone, Ida; Russo, Sara; Magon, Arianna; Conte, Gianluca; Guardamagna, Luca; Arrigoni, Cristina (Acta Biomedica Atenei Parmensis, 2022)
T2DM is a multifactorial disease, and it is considered a worldwide challenge for its increasing prevalence and its negative impact on patients’ wellbeing. Even if it is known that self-care is a key factor in reaching optimal outcomes, and males and females implement different self-care behaviors, sex-related differences in self-care of patients with T2DM have been poorly investigated. Especially, an overall view of the available evidence has not yet been done. Accordingly, this review aims to summarize, critically review, and interpret the available evidence related to the sex-related differences in self-care behaviors of patients with T2DM. An extensive literature review was performed with a narrative synthesis following the PRISMA statement and flowchart through four databases: PubMed, CINAHL, Scopus, and Embase. From the 5776 identified records by the queries, only 29 articles were included, having a high-quality evaluation. Both females and males with T2DM must improve their self-care: more males reported performing better behaviors aimed at maintaining health and clinical stability (i.e., self-care maintenance) than females, but mainly in relation to physical activity. On the other hand, more females reported performing adequate behaviors aimed at monitoring their signs and symptoms (i.e., self-care monitoring) but with worse glycemic control and diabetic complications (i.e., self-care management). This review firstly provides an overall view of different self-care behaviors implemented by males and females with T2DM, showing that self-care management should be improved in both sexes. Health education must include the problems related to the diabetic pathology and the patient’s own characteristics, such as sex.